#ProjectPresence: Highlighting black LGBTQ persons and communities to reduce stigma: A program evaluation. (February 2022) - Fields, Errol L.; Long, Amanda; Silvestri, Francesca; Bademosi, Kehinde; Benton-Denny, John; Granderson, Ricky; Schumacher, Christina; Chandran, Aruna; Greenbaum, Adena; Jennings, Jacky
Highlights: A photo campaign was used to address social marginalization of Black LGTBQ persons. Qualitative methods were used to explore perceptions of program influence on stigma. Themes of increased LGBTQ visibility, acceptance, and personal growth were found. Abstract: Etiologies of HIV disparities are multifaceted; anti-LGBTQ stigma and social marginalization are contributory factors. A city health department developed a program, #ProjectPresence, exhibiting professional photos of Black LGBTQ persons in public spaces. An academic partner explored the relationship of the program to visibility, anti-LGBTQ stigma and social marginalization of Black LGBTQ persons, i.e. models, directly involved in the program and their perceptions of these relationships more broadly for community members. Brief self-administered surveys and semi-structured, in-depth interviews with #ProjectPresence models (n = 15) were conducted after the program to gather their experiences before, during and after the program. Descriptive analyses of survey responses were conducted using Stata 15.1. Interviews were audio-recorded, transcribed and analyzed in NVivo10 using categorical analysis. Surveys indicated prevalent experiences of enacted stigma (73 %) and perceptions of poor local acceptance of LGBTQ people (53 %). Interviews suggested that the program may have influenced positive individual- and community-level changes by increasing visibility of LGBTQ communities and improving acceptance among non-LGBTQ persons, inspiring personal growth and self-acceptance among models, and providing opportunities to foster new connections among LGBTQ subpopulations. Our findings suggest similar programs may present promising approaches for the reduction of stigma and social marginalization affecting LGBTQ persons and communities.